2013
DOI: 10.1089/pho.2013.3561
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG Laser Irradiation of the Tooth Root Surface Inhibits Demineralization and Root Surface Softening Caused by Minocycline Application

Abstract: Objective: The aim of this study was to investigate the effect of laser irradiation on root surface demineralization caused by local drug delivery systems (DDS), and to evaluate the effect of sealing on drug retention. Background data: The duration of supportive periodontal treatment (SPT) has increased with increasing life expectancy. Repeated root planing and DDS application during SPT should be reconsidered with regard to their effects on the root surface. Methods: Extracted human teeth were collected, cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
3
0
3
Order By: Relevance
“…However, there are some disadvantages to this approach, such as the necessity for repeated treatments and its utility for small ranges of the periodontium. Additionally, the applied antimicrobial agents can cause decalcification and root surface softening [ 44 ].…”
Section: Periodontitismentioning
confidence: 99%
“…However, there are some disadvantages to this approach, such as the necessity for repeated treatments and its utility for small ranges of the periodontium. Additionally, the applied antimicrobial agents can cause decalcification and root surface softening [ 44 ].…”
Section: Periodontitismentioning
confidence: 99%
“…Nevertheless, it has been shown that systemic administration of antibiotics can exert some negative side effects, including antibiotic resistance. Local forms of antimicrobial application also have a number of disadvantages, such as the need to repeat treatments, the effect of rapid washing of the substance and, in addition, demineralization of the root surface [ 7 , 8 ]. Another harmful consequence is that SRP can open dentinal tubules, which can further offer access to periodontal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…A periodontite é uma doença comum que pode ocasionar perda dentária, e a principal causa da destruição do periodonto é a inflamação crônica através da ação bacteriana (Azarpazhooh et al, 2010). O controle e tratamento da infecção é feito por meio de raspagem e alisamento da superfície dental e radicular, utilizando instrumentos manuais, sendo algumas vezes necessário adicionar procedimentos cirúrgicos (Watanabe et al, 2013).…”
Section: Introductionunclassified